PERLINDUNGAN HUKUM TERHADAP MEREK TEKRENAL YANG TIDAK TERDAFTAR DI INDONESIA DALAM PUTUSAN MAHKAMAH AGUNG NOMOR 7 K/PDT.SUS-HKI/2018 - Nanda Resa Nur Aliska; Christine S.T. Kansil (Jurnal Hukum Adigama, 2021)
the position of the brand has an important role in the world of commerce, so it is very important to provide protection for the brand, which if the company's brand becomes widely known in the community, it will allow competitors who are not in good faith to commit piracy, imitate the brand, or even by counterfeiting to enrich yourself in a short span of time. The problems faced are how the system for granting trademark protection to brands that are not registered in Indonesia and how the legal protection for well-known brands that are not registered in Indonesia in the Supreme Court Decision Number 7K / Pdt.Sus-HKI / 2018. The research method used is normative juridical legal research. The results showed that the protection of foreign well-known marks that are not registered in Indonesia according to the Trademark Law is only protected for 5 (five) years, if the foreign wellknown mark is not registered, other people can register the name and claim the mark. Of course this is contrary to the theory of legal protection, where the state is obliged to protect a citizen/person, even though the person is a foreigner. Where there are 2 (two) kinds of protection methods, namely preventive and repressive methods. Preventive efforts are to prevent brand infringement, while repressive efforts if there is a trademark violation are through civil lawsuits or criminal charges.